Transthyretin Cardiac Amyloidosis: A Cardio-Orthopedic Disease - Federico Perfetto; Mattia Zampieri; Giulia Bandini; Roberto Fedi; Roberto Tarquini; Raffaella Santi; Luca Novelli; Marco Allinovi; Alessia Argirò; Francesco Cappelli (Biomedicines, 2022)
Orthopaedic manifestations of wild-type transthyretin amyloidosis are frequent and characteristic, including idiopathic bilateral carpal tunnel syndrome, idiopathic lumbar canal stenosis, atraumatic rupture of the brachial biceps tendon, and, more rarely, finger disease and rotator cuff. These manifestations often coexisting in the same patient, frequently male and aged, steadily precede cardiac involvement inducing a rapidly progressive heart failure with preserved ejection fraction. Although transthyretin cardiac amyloidosis remains a cardiac relevant disease, these extracardiac localisation may increase diagnostic suspicion and allow for early diagnosis assuming the role of useful diagnostic red flags, especially in light of new therapeutic opportunities that can slow or stop the progression of the disease. For the cardiologist, the recognition of these extracardiac red flags is of considerable importance to reinforce an otherwise less emerging diagnostic suspicion. For orthopedists and rheumatologists, the presence in an old patient with or without clinical manifestations of cardiovascular disease, of an unexpected and inexplicable constellation of musculoskeletal symptoms, can represent a fundamental moment for an early diagnosis and treatment is improving a patient’s outcome.